Dampak Penerapan Kultur Lokal Tri Hita Karana terhadap Orientasi Kewirausahaan dan Orientasi Pasar - I Gede Riana (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2011)
This study aims to investigate the impact of Tri Hita Karana culture toward entrepreneurial orientation and market orientation of SMEs of silver craft in Bali. The population of this research is all small and medium size enterprises of silver craft in Bali. By using purposive random sampling, 110 small and medium size enterprises located in four regencies in Bali were selected as samples. The data collection technique was distributing questionnaires. Furthermore, to test the inter-variabels influence, inferential analysis of Structural Equation Modeling (SEM) is applied using Partial Least Square (PLS) approach. The findings of this research are Tri Hita Karana culture could improve the entrepreneurial orientation and market orientation. It was also found that the entrepreneurial orientation influence the market orientation.